Evaluation of Self Medication among Students from Different Universities in Chittagong, Bangladesh - Jakaria, M; Hasant, A; Tarek, MI; Islam, MZ; Zaman, R; Parvez, M; Chowdhury, TA; Hasan, MI; Sayeed, MA; Ali, MH (Journal of Medicine, 2017)
Objective: We aimed to find out frequency of self medication among university students of Chittagong, Bangladesh by using a cross sectional questionnaire based survey study. Method: For this study, 439 students selected from nine universities of Chittagong through non-probability convenience sampling. Results: Among the total respondents, 278(63.32%) respondents were males and 161(36.67%) respondents were females. The most important reasons for self medication were no need to visit doctor for minor illness 227(51.70%) and quick relief 161(36.67%). Among the total respondents, 229(52.16%) used same direction of self medication of him/her for their family. The highest proportion of respondents 229(52.16%) did not check expiry date of medicine when they buy medicine from retail pharmacy. There were several conditions they had used self medications and the greatest number of students used to treat headache 273(62.18%) and fever 199(45.33%). The data reveals that the highest proportion, 243(55.35%) students learned medications from doctor prescription provided to cure their previous illness. The greatest number of students 398(90.66%) chooses allopathic medicine among four different system of medicine. The respondents used different allopathic drugs used in self medications where greatest number 296(67.42%) used analgesics. Conclusion: This study revealed that the prevalence and practices of self-medication among the university student and the greater part of students had a poor knowledge about proper self-medication whereas the knowledge of the benefits and risks were not adequate. J MEDICINE January 2017; 18 (1) : 15-20